Assessment of motor skills associations with executive functioning in children of senior preschool age - T.V. Zhilyaeva; E.M. Tolstobrova; O.M. Silantyeva; U.A. Nasonova; I.V. Brak; V.Yu. Borisov; Yu.M. Taraday; A.M. Borisova (Психологическая наука и образование)
Context and relevance. The article examines the relationship between motor skills (fine and gross motor skills, motor reaction time) and executive functioning (EF), which is the most important predictor of future academic success. Objective. This experimental study is designed to determine the strength and direction of associations between EF components (planning ability, working memory, inhibitory control) and various motor skills (gross and fine motor skills) in older preschool children. Hypothesis. In preschool children, EF components (planning ability, working memory, inhibitory control) have close associations with various indicators of motor development, but so far, this has not been unambiguously confirmed in experimental studies. Methods and materials. The examination of the participants was conducted within the framework of the project "Study of neurobiological predictors of academic success in children" (Priority 2030) using the hardware and software system SHUHFRIED (Tower of London – Freiburg version, TOL-F; Motor Learning Skills test, short form according to Sturm and Büssing, MLS; Reaction Time test, RT; n = 81, 58 boys, average age 6,42 ± 0,53 years) and the stabilometric complex ST-150 (65 children, 52 boys, average age 6,4 ± 0,52 years). Results. According to the correlation analysis of the stabilometry and TOL-F test indices, the lower the gross motor skills (postural stability) indices, the better the planning and working memory indices; however, the inhibitory control index directly correlates with postural stability skills. The results of the fine motor skills and EF tests mostly agree with each other; however, they have lateralization characteristics, and the size of the correlation coefficients does not exceed 0.4. Conclusions. The correlations of the fine motor skills test results with EF are mostly weak. Probably, at the preschool education stage, the impact only on the motor sphere (fine motor skills in particular) is not a sufficient condition for the development of EF. Planning and working memory inversely correlate with the gross motor skills development indices, which probably indicates a reciprocal relationship between individual higher cortical functions and gross motor skills in older preschool age.